(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-171-181 This study was conducted to determine the functions of the creolized text and to identify the percentage of such texts on Russian news sites. The study proved that more than 2/3 of Russian news sites use creolization. The main functions of creolized texts are determined: improving the quality of the design and content of the site, enriching with a large amount of information, improving its transmission and perception, optimizing the image in search engines. The study was carried out using the methods of analysis, synthesis, classification and measurement. Key words: creolized texts, news sites, infographics, campion attribute, buttons and icons